Membangun Restoratif Justice Menuju Pembaruan Kitab Undang-Undang Hukum Acara Pidana - Krismiyarsi Krismiyarsi (SPEKTRUM HUKUM, 2025)
The process of resolving criminal cases through restorative justice is still fragmented across separate law-enforcement institutions, namely: the Police through Police Regulation (Perpol) No. 8 of 2021, the Prosecution Service through Attorney General Regulation (Perja) No. 15 of 2020, and the Courts through Supreme Court Regulation (Perma) No. 1 of 2024. To date, there has been no statute that specifically regulates the mechanism for resolving criminal cases through restorative justice. The enactment of Law No. 1 of 2023 on the Criminal Code (Kitab Undang-Undang Hukum Pidana/KUHP) brings fresh hope, as it implicitly recognizes restorative justice. This can be seen in the formulation of Article 54 letter (j) on sentencing guidelines, which requires judges, when imposing a sentence, to consider forgiveness from the victim and/or the victim’s family; Article 70 letter (e), which provides that imprisonment should, as far as possible, not be imposed if it is found that the defendant has paid compensation to the victim; and Article 132, which states that prosecutorial authority is extinguished if there has been a settlement outside the court process as regulated in a law. Article 132 mandates the existence of a statute to further regulate restorative justice; however, up to the present, no such law has been enacted. This study employs a normative juridical research approach, using secondary data sources and qualitative analysis. The research aims to develop an effective restorative justice framework by analyzing factors of substance, structure, and legal culture that may influence the effectiveness of restorative justice in future implementation, so that the findings can contribute input for the forthcoming reform of the Criminal Procedure Code (KUHAP).